Analisis Penilaian Materi Ahli Berdasarkan Pembelajaran Berbasis Proyek - Jamaluddin Ahmad; mita yuliana (Universitas Muhammadiyah Bangka Belitung, 2019)
Teaching materials is one of the important factor in supporting on learning process. The teacher and student need learning materials which help them to acquire the learning objectives. The arrangement of learning material based on learning model is needed to be judged by the experts. This paper is supposed to present and to analyze the experts’ judgments towards theme based learning material based on project based learning. The instrument of this research was the experts’ validation instrument. Meanwhile, the subjects of the research were 9 experts. The result of the research showed 86% from material experts, 88% from language experts, and 89,6% from media experts. Based on the result, it can be concluded that theme based learning material based on project based learning was proper enough to be used but still need some revision in the future.